You are on page 1of 3

MATH 1005H Fall 2015

Test One Solutions


1. (6 marks) Solve the initial-value problem
3x2 − sin(x)
2y 0 = , y(0) = −3.
y
Solution: This is a separable equation. Rearranging, we have
2yy 0 = 3x2 − sin(x).
Integrating with respect to x (and using the substitution rule on the left) yields
Z Z
2ydy = (3x2 − sin(x))dx

y 2 = x3 + cos(x) + c.
p
Thus y = ± x3 + cos(x) + c is the general solution. Since y(0) = −3, we have

−3 = ± 1 + c.
Thus we must choose the negative sign and set 1 + c = 9, and so c = 8. The
solution to the initial value problem is
p
y = − x3 + cos(x) + 8.

2. (6 marks) Find the general solution of the equation


xy 0 = y 1 + ln(y) − ln(x) , x > 0, y > 0.


Solution: Rearranging, we have


y  y 
y0 =
1 + ln .
x x
This is a homogeneous equation. We set u = xy , so that y = ux and y 0 = u+xu0 .
Then
u + xu0 = u(1 + ln(u)).
Rearranging, we have
1 1
u0 = .
u ln(u) x
This is a separable equation. Integrating both sides with respect to x (and using
the substitution rule on the left), we have
Z Z
1 1
du = dx
u ln(u) x
ln | ln(u)| = ln |x| + c1
| ln(u)| = ec1 |x|
ln(u) = ±ec1 x
ln(u) = cx
u = ecx

1
(to evaluate the integral on the left, the substitution t = ln(u) may be made).
Thus
y = xu = xecx
is the general solution.

3. (6 marks) Find the general solution of the equation

x2 y 0 + 2x2 y = x6 + x3 .

Solution: This is a linear equation. We divide by x2 to put it in standard form:

y 0 + 2y = x4 + x.

We choose the integrating factor


R
2dx
I(x) = e = e2x .

Multiplying the equation by e2x yields

e2x y 0 + 2e2x y = e2x x4 + e2x x


(e2x y)0 = e2x x4 + e2x x.

We integrate to get
Z Z
2x 2x 4 2x
e2x x4 + x dx.
 
e y= e x + e x dx =

The integral can be evaluated by using the table method or by applying integra-
tion by parts repeatedly (for what it’s worth, there was a typo in the question.
I had intended this integral to be easier to evaluate! Markers were asked to be
fairly lenient with this integral). Doing this, we have
 
2x 2x 1 4 3 3 2 1
e y=e x −x + x −x+ + c.
2 2 2
Thus the general solution is
1 3 1
y = x4 − x3 + x2 − x + + ce−2x .
2 2 2

4. (6 marks) Find the general solution of

2xey + (x2 ey + 4y 3 )y 0 = 0.

Solution: We have Py = 2xey and Qx = 2xey . The equation is exact because


Py and Qx are continuous in the entire plane (which is simply connected), and
Py = Qx . A potential function f exists. We use the fact that fx = P and
integrate with respect to x to get

f (x, y) = x2 ey + g(y).

2
We now use the fact that we must have fy = Q to get

x2 ey + g 0 (y) = x2 ey + 4y 3 .

Thus g 0 (y) = 4y 3 and so g(y) = y 4 + c1 . A potential function is

f (x, y) = x2 ey + y 4 + c1 .

To get the solution of the equation, we set f (x, y) = c2 . Combining constants,


this yields the solution
x2 ey + y 4 = k.

5. (6 marks) Find the general solution of the equation

y 0 + y = −2e2x y 2 .

Solution: This is a Bernoulli equation with α = 2. We set u = y 1−α = y −1 .


Then y = u−1 , and so y 2 = u−2 and y 0 = −u−2 u0 . Substituting this in to the
equation, we get
−u−2 u0 + u−1 = −2e2x u−2 .
Multiplying by −u2 yields
u0 − u = 2e2x .
This is a linear equation. We choose the integrating factor
R
−1dx
I(x) = e = e−x .

Multiplying the equation by e−x yields

e−x u0 − e−x u = 2ex


(e−x u)0 = 2ex .

We integrate to get

e−x u = 2ex + c
u = 2e2x + cex .

Thus the general solution is


1
y = u−1 = .
2e2x + cex